Ellipsoidal Design of Robust Secure Frequency Control in Smart Cities Under Denial-of-Service Cyberattack - Hisham Soliman; Ehab Bayoumi; Sangkeum Lee (Smart Cities)
To meet the requirements of a smart city in supporting a sustainable high-quality lifestyle for people, there is a need for many smart technologies and smart grids. A smart grid integrates electrical and digital technologies, information, and communication. Microgrids (MGs) are the main components of smart grids. The proposed control scheme introduces a robust control mechanism against model uncertainties and is secure against communication cyberattacks. A novel design criterion is formulated as linear matrix inequalities (LMIs) to provide the required state feedback with integral control. In contrast to the conventional H∞ control approach, the suggested tracker offers enhanced disturbance attenuation and a faster response. Different testing scenarios demonstrate the successful performance of the suggested controller.